The effect of Bruton's tyrosine kinase (BTK) inhibitors on collagen‐induced platelet aggregation, BTK, and tyrosine kinase expressed in hepatocellular carcinoma (TEC). (24th September 2018) - Chen, Jun; Kinoshita, Taisei; Gururaja, Tarikere; Sukbuntherng, Juthamas; James, Danelle; Lu, Daniel; Whang, Jennifer; Versele, Matthias; Chang, Betty Y.
Abstract: Objectives: Bruton's tyrosine kinase (BTK) and tyrosine kinase expressed in hepatocellular carcinoma (TEC) are expressed by human platelets. These kinases participate in platelet activation through the collagen receptor glycoprotein VI and may perform overlapping functions. In clinical studies, BTK inhibitors (ibrutinib, acalabrutinib, tirabrutinib, zanubrutinib) have been associated with increased bleeding risk, which may result from inhibition of BTK alone or of both BTK and TEC, although the role of TEC in bleeding risk remains unclear. Methods: Here, in vitro catalytic and binding activities of ibrutinib and acalabrutinib were determined with four assay systems. Platelet aggregation assays determined inhibitor potency and its relationship to selectivity between BTK and TEC. Results: Neither inhibitor was substantially more selective for BTK over TEC. The potencies at which BTK inhibitors suppressed platelet aggregation correlated with the potencies in on‐target BTK assays, including those in cells. At clinically relevant plasma concentration, ibrutinib, acalabrutinib, and tirabrutinib inhibited collagen‐induced platelet aggregation to a similar extent, despite differing in vitro IC50 s. Conclusions: Our results suggest BTK inhibition is the primary driver for inhibition of platelet aggregation. The subtle differences between these inhibitors suggest only randomized, double‐blind, placebo‐controlled clinical studies can fully address the bleeding risks of different BTK inhibitors.